COMPARISON OF SILAGE COMPOSITIONS OBTAINED FROM SOWN GRASSES AND NATURAL MEADOW GRASS IN FARM BĒRZI AND FARM LAIMĪTES - Kolneja, Vilma; Cimermane, Inese; Kaša, Marlinda (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
The paper deals with the methods of improving animal husbandry feed rations in two different farms. Forage quality in herd has enormous impact on methane production all over the world, so it is important to find ways to decrease these numbers and also increase the productivity of the whole herd. As a result of research, the chemical composition of the different kind silage of sown grasses and natural meadows will be clarified and proposals are developed for improvement the quality of feed for herd productivity increase.